Penentuan Optimalisasi Defisiensi Nutrisi Pada Praktikum Fisiologi Tumbuhan Di Laboratorium Secara Hidroponik (Sistem Sumbu Dan Tanpa Sumbu) - Sumiati; M. Akmal Surur (Universitas Muhammadiyah Prof. Dr. Hamka, 2021)
Background: Hydroponics is a method of agriculture that utilizes water as a planting medium. The purpose of the study was to find out good working procedures and nutrient solution formulas capable of showing symptoms of morphological nutritional deficiencies in plants. Methods: The plants used are the seeds of kale plants that are sown within 1 - 2 weeks (until roots, stems, and leaves grow). The design used is Random Group using three formulas with nine kinds of treatment on each formula and three repeats. Experiments were conducted on two hydroponic systems, the axis and without the axis. The parameters observed are the number of leaves, the leaves' length, the leaves' width, the plant's height, and the plant's height. Results: Observational data in the analysis using SPSS 25. The effect of treatment with test parameters is seen using ANOVA analysis and BNT advanced tests. Visual observations showed the formula of nutrient solutions 1, 2 and 3 using both the axis system and without the axis showed symptoms of nutritional deficiencies in kale plants. The axis less system experiment gave more significant results on all parameters except PD (leaf length) than the axis system based on the average results of BNT advanced tests. Conclusion: Nutrient solutions 1, 2 and 3 have a real effect on all test parameters.